Homeostatically Maintained Resting Naive CD4+ T Cells Resist Latent HIV Reactivation - Tsunetsugu-Yokota, Yasuko; Kobayahi-Ishihara, Mie; Wada, Yamato; Terahara, Kazutaka; Takeyama, Haruko; Kawana-Tachikawa, Ai; Tokunaga, Kenzo; Yamagishi, Makoto; Martinez, Javier P.; Meyerhans, Andreas (Frontiers in Microbiology, 2016)
Homeostatic proliferation (HSP) is a major mechanism by which long-lived naïve and memory CD4+ T cells are maintained in vivo and suggested to contribute to the persistence of the latent HIV-1 reservoir. However, while many in vitro latency models rely on CD4+ T cells that were initially differentiated via T-cell receptor stimulation (TCR) into memory/effector cells, latent infection of naïve resting CD4+ T cells maintained under HSP conditions has not been fully addressed. Here we describe an in vitro HSP culture system utilizing the cytokines IL-7 and IL-15 that allows studying latency in naïve resting CD4+ T cells. CD4+ T cells isolated from several healthy donors were infected with HIV pseudotypes expressing GFP and cultured under HSP conditions or TCR conditions as control. Cell proliferation, phenotype and GFP expression were analyzed by flow cytometry. RNA expression was quantified by qRT-PCR. Under HSP culture conditions, latently HIV-1 infected naïve cells are in part maintained in the non-dividing (= resting) state. Although a few HIV-1 provirus+ cells were present in these resting GFP negative cells, the estimated level of GFP transcripts per infected cell seems to indicate a block at the post-transcriptional level. Interestingly, neither TCR nor the prototypic HDAC inhibitor SAHA were able to reactivate HIV-1 provirus from these cells. This lack of reactivation was not due to methylation of the HIV LTR. These results point to a mechanism of HIV control in HSP-cultured resting naïve CD4+ T cells that may be distinct from that in TCR-stimulated memory/effector T cells.